Rapid Detection of Rifampin Resistance in Mycobacterium tuberculosis Isolates by Heteroduplex Analysis and Determination of Rifamycin Cross-Resistance in Rifampin-Resistant Isolates - Sarıbaş, Zeynep (American Society for Microbiology, 2003)
Direct heteroduplex analysis and a universal heteroduplex generator assay were performed to detect rifampin resistance rapidly in Turkish Mycobacterium tuberculosis isolates. Cross-resistance to rifapentine, rifabutin, and rifalazil was investigated. A relationship between specific mutations and resistance patterns, which can guide the choice of an appropriate therapeutic regimen for tuberculosis patients, was identified.